Simulation and evaluation of fuel distribution line from fuel terminal Tuban into integrated terminal Perak at PT Pertamina MOR V through ASPEN Plus® modeling - Budiman, Yosef; Pratiwi, Dwita Cahaya; Rofiqah, Umi; Puspasari, Ifa; Wibowo, Yudha Whastu; Khotip, Moh.; Vebriono, Hendrix Eko; Hidayat, Arif (Jurnal Rekayasa Proses, 2024)
This research aims to 1) to determine operating conditions that correspond to the amount of fuel needed to be distributed, 2) visualize the profile of pressure changes with pipe distance, and 3) compare actual conditions with simulated conditions. The research method consists of simulation of energy loss in the form of pressure drop for each type of fuel oil (gasoline and gasoil) using ASPEN Plus® software. Research results show that a greater pump pressure of 87 bar is required to distribute gasoil, compared to gasoline which only uses 82 bar to reach ideal atmospheric pressure at 750 m3/hour. Reduction in fuel pumping pressure is close to linearity, where pumping pressure will continue to decrease as piping distribution distance increases. % error is obtained by comparing the simulation results with the industrial standard which is evidenced by % error of 7.69 (moderate) in the type of gasoline fuel and % error value of 1.81 (strong) in the type of gasoil fuel. This research has been in accordance with the real conditions in the field, so it can predict the right conditions to maximize the process.